2016
DOI: 10.1103/physreva.93.063820
|View full text |Cite
|
Sign up to set email alerts
|

Time-local Heisenberg-Langevin equations and the driven qubit

Abstract: The time-local master equation for a driven boson system interacting with a boson environment is derived by way of a time-local Heisenberg-Langevin equation. Extension to the driven qubit fails-except for weak excitation-due to the lost linearity of the system-environment interaction. We show that a reported time-local master equation for the driven qubit is incorrect. As a corollary to our demonstration, we also uncover odd asymptotic behavior in the "repackaged" time-local dynamics of a system driven to a fa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Appendix A. Derivation of Eq. (26) We briefly discuss here the reason why Eq. (26) is true whenever Φ (m) is divisible, for all m. We can define an auxiliary map Φ t that satisfies…”
mentioning
confidence: 99%
“…Appendix A. Derivation of Eq. (26) We briefly discuss here the reason why Eq. (26) is true whenever Φ (m) is divisible, for all m. We can define an auxiliary map Φ t that satisfies…”
mentioning
confidence: 99%
“…The first setup we consider is a two-level system (2LS) in front of a mirror. [39,47,52,58,63,69,70] The 2LS is pumped with a pulsed laser field Ω(t) which controls the emission statistics via its pulse area A. Looking at the emission without feedback, we observe that for a pulse with A = the 2LS is inverted and acts as a single-photon source.…”
Section: Selective Control Of Individual Photon Probabilitiesmentioning
confidence: 99%
“…As a consequence, the non-Markovianity of the dynamics needs to be taken into account. [37][38][39][40][41][42][43][44][45][46] Various setups to control quantum few-level systems via timedelayed feedback have been studied theoretically and it has been shown that it is possible to control characteristic quantities such as the photon-photon correlation and the concurrence which functions as a measure of entanglement. [47][48][49][50][51][52][53][54][55][56][57][58][59] In these systems, in general, the control parameters that can be used to evoke the desired behavior are the delay time and the characteristic frequency which, depending on the considered setup, can be, for example, the frequency of an involved optical transition or the frequency of a cavity mode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An example of such a structured reservoir that we consider is a coherent, feedback-type, reservoir-LB interaction, which can be used to steer the dynamics of the TLE with the goal of coherence preservation. Moreover, even though there are numerical methods that in principle are capable of characterizing the effect of quantum coherent feedback at a finite temperature [65,66], to our knowledge, this is the first work to report on the exact influence of this effect on the amount of recovered coherence.…”
Section: Introductionmentioning
confidence: 99%